Synthesis, Spectroscopic, Molecular Structure, and Antibacterial Studies of Dibutyltin(IV) Schiff Base Complexes Derived from Phenylalanine, Isoleucine, and Glycine - Har Lal Singh; Jangbhadur Singh (Bioinorganic Chemistry and Applications)
New series of organotin(IV) complexes and Schiff bases derived from amino acids have been designed and synthesized from condensation of 1H-indole-2,3-dione, 5-chloro-1H-indole-2,3-dione, and α-amino acids (phenylalanine, isoleucine, and glycine). All compounds are characterized by elemental analyses, molar conductance measurements, and molecular weight determinations. Bonding of these complexes is discussed in terms of their UV-visible, infrared, and nuclear magnetic resonance (1H, 13C, and 119Sn NMR) spectral studies. The results suggest that Schiff bases behave as monobasic bidentate ligands and coordinate with dibutyltin(IV) in octahedral geometry according to the general formula [Bu2Sn(L)2]. Elemental analyses and NMR spectral data of the ligands with their dibutyltin(IV) complexes agree with their proposed distorted octahedral structures. Few representative compounds are tested for their in vitro antibacterial activity against Gram-positive (B. cereus, Staphylococcus spp.) and Gram-negative (E. coli, Klebsiella spp.) bacteria. The results show that the dibutyltin complexes are more reactive with respect to their corresponding Schiff base ligands.